The Role of the Educational Developer in the Improvement of University Teaching - Wilcox, Susan (Canadian Journal of Higher Education, 1998)
As educational development (ED) programs become entrenched in many universities and a growing number of academics are engaged in educational development work, it is important that the nature of the ED occupation/profession is defined. The study reported in this paper examined the characteristics of persons holding educational development appointments in Ontario universities. The intent was to develop an accurate picture of the respondents as a professional group. The study provides insight into how educational developers make sense of their work.